Good practices and ethical issues in food safety related research - Rallou Thomopoulos; Pierre Bisquert; Bart van der Burg; Erwan Engel (Elsevier, 2022)
After introducing a historical view of research ethics and the main schools of thought, the paper is structured around two main topics: On the one hand, the protection of the environment surrounding the research experiments conducted, which is a major aspect in food safety related research and includes the staff carrying out the research. On the other hand, collective decision aspects, which are involved in the construction of decision support systems for food safety enhancement. Based on a few examples in food safety related research, the paper reviews the ethical issues considered, the ethical principles applied, and the main measures taken in these cases.